Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Spin decontamination for magnetic dipolar coupling calculations: Application to high-spin molecules and solid-state spin qubits - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review Research)

Tetracene Ultrathin Film Growth on Hydrogen-Passivated Silicon - Niederhausen, Jens; MacQueen, Rowan W.; Lips, Klaus; Aldahhak, Hazem; Schmidt, Wolf Gero; Gerstmann, Uwe (Langmuir)

Photochemical Ring Opening of Oxirane Modeled by Constrained Density Functional Theory - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (ACS Omega)

Carrier-wave population transfer in semiconductors - Zuo, R; Song, X; Meier, Torsten; Yang, W (Journal of Physics: Conference Series)

Transfer function replacement of phenomenological single-mode equations in semiconductor microcavity modeling - Carcamo, M.; Schumacher, Stefan; Binder, R. (Applied Optics)
Semiconductor microcavities are frequently studied in the context of semiconductor lasers and in application-oriented fundamental research on topics such as linear and nonlinear polariton systems, polariton lasers, polariton pattern formation, and polaritonic Bose–Einstein condensates. A commonly used approach to describe theoretical properties includes a phenomenological single-mode equation that complements the equation for the nonlinear optical response (interband polarization) of the semiconductor. Here, we show how to replace the single-mode equation by a fully predictive transfer function method that, in contrast to the single-mode equation, accounts for propagation, retardation, and pulse-filtering effects of the incident light field traversing the distributed Bragg reflector (DBR) mirrors, without substantially increasing the numerical complexity of the solution. As examples, we use cavities containing GaAs quantum wells and transition-metal dichalcogenides (TMDs).
Keywords: Atomic and Molecular Physics; and Optics; Engineering (miscellaneous); Electrical and Electronic Engineering

Chiral condensates in a polariton hexagonal ring. - Ma, Xuekai; Kartashov, YV; Kavokin, A; Schumacher, Stefan (Optics Letters)

Electron paramagnetic resonance study of ferroelectric phase transition and dynamic effects in a Mn2+ doped [NH4][Zn(HCOO)3] hybrid formate framework - Navickas, Marius; Giriūnas, Laisvydas; Kalendra, Vidmantas; Biktagirov, Timur; Gerstmann, Uwe; Schmidt, Wolf Gero; Mączka, Mirosław; Pöppl, Andreas; Banys, Jūras; Šimėnas, Mantas (Physical Chemistry Chemical Physics)
EPR spectroscopy reveals the universality class and dynamic effects of the [NH4][Zn(HCOO)3] hybrid formate framework.

Photocatalytic properties of graphene‐supported titania clusters from density‐functional theory - Badalov, Sabuhi; Wilhelm, René; Schmidt, Wolf Gero (Journal of Computational Chemistry)
Density-functional theory calculations of (TiO2)n clusters (n = 1–5) in the gas phase and adsorbed on pristine graphene as well as graphene quantum dots are presented. The cluster adsorption is found to be dominated by van der Waals forces. The electronic structure and in particular the excitation energies of the bare clusters and the TiO2/graphene composites are found to vary largely in dependence on the size of the respective constituents. This holds in particular for the energy and the spatial localization of the highest occupied and lowest unoccupied molecular orbitals. In addition to a substantial gap narrowing, a pronounced separation of photoexcited electrons and holes is predicted in some instances. This is expected to prolong the lifetime of photoexcited carriers. Altogether, TiO2/graphene composites are predicted to be promising photocatalysts with improved electronic and photocatalytic properties compared to bulk TiO2.

Accurate photon echo timing by optical freezing of exciton dephasing and rephasing in quantum dots - Kosarev, Alexander N.; Rose, Hendrik; Poltavtsev, Sergey V.; Reichelt, Matthias; Schneider, Christian; Kamp, Martin; Höfling, Sven; Bayer, Manfred; Meier, Torsten; Akimov, Ilya A. (Communications Physics)
Abstract Semiconductor quantum dots are excellent candidates for ultrafast coherent manipulation of qubits by laser pulses on picosecond timescales or even faster. In inhomogeneous ensembles a macroscopic optical polarization decays rapidly due to dephasing, which, however, is reversible in photon echoes carrying complete information about the coherent ensemble dynamics. Control of the echo emission time is mandatory for applications. Here, we propose a concept to reach this goal. In a two-pulse photon echo sequence, we apply an additional resonant control pulse with multiple of 2 π area. Depending on its arrival time, the control slows down dephasing or rephasing of the exciton ensemble during its action. We demonstrate for self-assembled (In,Ga)As quantum dots that the photon echo emission time can be retarded or advanced by up to 5 ps relative to its nominal appearance time without control. This versatile protocol may be used to obtain significantly longer temporal shifts for suitably tailored control pulses.

Realization of all-optical vortex switching in exciton-polariton condensates - Meier, Torsten; Ma, Xuekai; Berger, Bernd; Aßmann, Marc; Driben, Rodislav; Schneider, Christian; Höfling, Sven; Schumacher, Stefan (Nature communications)
Vortices are topological objects representing the circular motion of a fluid. With their additional degree of freedom, the vorticity, they have been widely investigated in many physical systems and different materials for fundamental interest and for applications in data storage and information processing. Vortices have also been observed in non-equilibrium exciton-polariton condensates in planar semiconductor microcavities. There they appear spontaneously or can be created and pinned in space using ring-shaped optical excitation profiles. However, using the vortex state for information processing not only requires creation of a vortex but also efficient control over the vortex after its creation. Here we demonstrate a simple approach to control and switch a localized polariton vortex between opposite states. In our scheme, both the optical control of vorticity and its detection through the orbital angular momentum of the emitted light are implemented in a robust and practical manner.

k.p-based multiband simulations of non-degenerate two-photon absorption in bulk GaAs - Hannes, Wolf-Rüdiger; Meier, Torsten (Ultrafast Phenomena and Nanophotonics XXIV)

Strongly nonresonant four-wave mixing in semiconductors - Hannes, W.-R.; Trautmann, Alexander; Stein, M.; Schäfer, F.; Koch, M.; Meier, Torsten (Physical Review B)

Enhanced high-order harmonic generation in semiconductors by excitation with multicolor pulses - Song, Xiaohong; Yang, Shidong; Zuo, Ruixin; Meier, Torsten; Yang, Weifeng (Physical Review A)

Understanding gray track formation in KTP: Ti^3+ centers studied from first principles - Bocchini, Adriana; Eigner, Christof; Silberhorn, Christine; Schmidt, Wolf Gero; Gerstmann, Uwe (Phys. Rev. Materials)

The Influence of Hydrothermal Aging on the Material Properties of Continuous Fiber-Reinforced Thermoplastics and its Non-Destructive Characterization - Moritzer, Elmar; Hüttner, M.; Henning, Bernd; Webersen, Manuel (Advances in Polymer Processing 2020)

Improving the performance of household refrigerating appliances through the integration of phase change materials in the context of the new global refrigerator standard IEC 62552:2015 - Sonnenrein, Gerrit; Baumhögger, Elmar; Elsner, Andreas; Morbach, A.; Neukötter, Moritz; Paul, Andreas; Vrabec, J. (International Journal of Refrigeration)
The influence of latent heat storage elements on the cooling performance and the temperature rise time of household refrigerating appliances is studied experimentally in the context of the “new global refriger- ator standard”IEC 62552:2015. In addition to the daily energy consumption, this international standard- ization introduced performance tests for cooling capacity and temperature rise time. While the cooling capacity has long been anchored in various test procedures of consumer organizations, the temperature rise time, which has only been tested on freezers so far, will be a decisive factor in the future. Moreover, the need for so-called "smart appliances" that may balance power consumption is increasing since such devices may compensate the volatility of renewable energies and thus stabilize the power grid. Against this background, eight commercial household refrigerators and refrigerator-freezers are equipped with polymer-bound phase change materials (PCM) and their performance is determined under the new stan- dard test conditions. The results show that the introduction of PCM increases the cooling capacity by up to 33 % and also increases the temperature rise time by up to 145 %, without affecting power consump- tion, as compared to the unmodified refrigeration appliances.

A micromechanical-based finite element simulation of process-induced residual stresses in metal-CFRP-hybrid structures - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Composite Structures)

Realization of all-optical vortex switching in exciton-polariton condensates - Ma, Xuekai; Berger, B; Aßmann, M; Driben, R; Meier, Torsten; Schneider, C; Höfling, S; Schumacher, Stefan (Nature Communications)

Long- and Short-Term Tensile Strength and Morphology of Joined Beta-Nucleated Polypropylene Parts - Wübbeke, Andrea; Schöppner, Volker; Paul, André; Tiemann, Michael; Austermeier, Laura; Fitze, Marcus; Chen, Mingie; Jakob, Fabian; Heim, Hans-Peter; Wu, Tao; Niendorf, Thomas; Röhricht, Marie-Luise; et al. (SPE ANTEC 2020: The Virtual Edition 5)
This paper presents the results of static short-term and long-term tensile tests for beta-nucleated joined polypropylene samples by the hot plate welding process. In the present study different dimensionless joining displacements are accounted for. The results show that high short-term tensile strength does not directly transfer to high long-term tensile strength. The morphology of the weld seam in the joined samples is examined by means of transmitted and reflected light microscopy. For the dimensionless joining displacements of 0.75 and 0.95, stretched spherulites are obtained. X-Ray diffraction can be used as a tool for qualitative and quantitative analysis and eventually for differentiation of samples of various joining displacements.

Investigation of residual stresses of hot plate welding - Schöppner, Volker; Wübbeke, Andrea; Geißler, B.; Schmidt, M.; Maginer, A.; Wu, T.; Niendorf, T.; Jakob, F.; Heim, H. (73rd Annual Assembly of the International Institute of Welding (IIW))

Selected Aspects for the Assessment of Laser Transmission Welding - Schöppner, Volker; Wübbeke, Andrea; Schriegel, Fabian; Paul, Andrej; Tiemann, Michael; Geißler, Bastian; Schmidt, Michael; Magnier, Arnaud; Niendorf, Thomas (Joining Plastics)
In diesem Artikel werden das Scherzugverhalten und der morphologische Zustand von konturgeschweißtem Polypropylen (PP) mit einem Massenanteil von 0,2% Ruß untersucht. Dabei zeigen die Ergebnisse ...

LONG- AND SHORT-TERM TENSILE STRENGTH AND MORPHOLOGY OF JOINED BETA-NUCLEATED POLYPROPYLENE PARTS - Schöppner, Volker; Wübbeke, Andrea; Paul, A.; Tiemann, M.; Austermeier, Laura; Fitze, M.; Chen, M.; Jakob, F.; Heim, H.-P-; Wu, T.; Niendorf, T.; Röhricht, M.-L.; et al. (ANTEC20)

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

Influence of Microstructure in Near‐Surface Areas of Feedstocks on the Bond Strength of Roll Bonded Aluminum Clads - Grydin, Olexandr; Matzelt, Manuel; Andreiev, Anatolii; Frolov, Yaroslav; Schaper, Mirko (Advanced Engineering Materials)

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslaw; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)

Sprachsensible Formulierung von Erhebungsinstrumenten - Schwabl, Franziska; Janssen, Elmar A.; Sloane, Peter F. E. (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

CP2K: An electronic structure and molecular dynamics software package - Quickstep: Efficient and accurate electronic structure calculations - Kühne, Thomas; Iannuzzi, Marcella; Ben, Mauro Del; Rybkin, Vladimir V.; Seewald, Patrick; Stein, Frederick; Laino, Teodoro; Khaliullin, Rustam Z.; Schütt, Ole; Schiffmann, Florian; Golze, Dorothea; Wilhelm, Jan; et al. (The Journal of Chemical Physics)
CP2K is an open source electronic structure and molecular dynamics software package to perform atomistic simulations of solid-state, liquid, molecular, and biological systems. It is especially aimed at massively parallel and linear-scaling electronic structure methods and state-of-theart ab initio molecular dynamics simulations. Excellent performance for electronic structure calculations is achieved using novel algorithms implemented for modern high-performance computing systems. This review revisits the main capabilities of CP2K to perform efficient and accurate electronic structure simulations. The emphasis is put on density functional theory and multiple post–Hartree–Fock methods using the Gaussian and plane wave approach and its augmented all-electron extension.

A Submatrix-Based Method for Approximate Matrix Function Evaluation in the Quantum Chemistry Code CP2K - Lass, Michael; Schade, Robert; Kühne, Thomas; Plessl, Christian (Proc. International Conference for High Performance Computing, Networking, Storage and Analysis (SC))
Electronic structure calculations based on density-functional theory (DFT) represent a significant part of today's HPC workloads and pose high demands on high-performance computing resources. To perform these quantum-mechanical DFT calculations on complex large-scale systems, so-called linear scaling methods instead of conventional cubic scaling methods are required. In this work, we take up the idea of the submatrix method and apply it to the DFT computations in the software package CP2K. For that purpose, we transform the underlying numeric operations on distributed, large, sparse matrices into computations on local, much smaller and nearly dense matrices. This allows us to exploit the full floating-point performance of modern CPUs and to make use of dedicated accelerator hardware, where performance has been limited by memory bandwidth before. We demonstrate both functionality and performance of our implementation and show how it can be accelerated with GPUs and FPGAs.

Evaluating FPGA Accelerator Performance with a Parameterized OpenCL Adaptation of Selected Benchmarks of the HPCChallenge Benchmark Suite - Meyer, Marius; Kenter, Tobias; Plessl, Christian (2020 IEEE/ACM International Workshop on Heterogeneous High-performance Reconfigurable Computing (H2RC))
FPGAs have found increasing adoption in data center applications since a new generation of high-level tools have become available which noticeably reduce development time for FPGA accelerators and still provide high-quality results. There is, however, no high-level benchmark suite available, which specifically enables a comparison of FPGA architectures, programming tools, and libraries for HPC applications. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community. To fill this gap, we have developed an OpenCL-based open-source implementation of the HPCC benchmark suite for Xilinx and Intel FPGAs. This benchmark can serve to analyze the current capabilities of FPGA devices, cards, and development tool flows, track progress over time, and point out specific difficulties for FPGA acceleration in the HPC domain. Additionally, the benchmark documents proven performance optimization patterns. We will continue optimizing and porting the benchmark for new generations of FPGAs and design tools and encourage active participation to create a valuable tool for the community.
Keywords: FPGA; OpenCL; High Level Synthesis; HPC benchmarking

Accurate Sampling with Noisy Forces from Approximate Computing - Rengaraj, Varadarajan; Lass, Michael; Plessl, Christian; Kühne, Thomas (Computation)
In scientific computing, the acceleration of atomistic computer simulations by means of custom hardware is finding ever-growing application. A major limitation, however, is that the high efficiency in terms of performance and low power consumption entails the massive usage of low precision computing units. Here, based on the approximate computing paradigm, we present an algorithmic method to compensate for numerical inaccuracies due to low accuracy arithmetic operations rigorously, yet still obtaining exact expectation values using a properly modified Langevin-type equation.

Oracle complexity classes and local measurements on physical Hamiltonians - Gharibian, Sevag; Piddock, Stephen; Yirka, Justin (Proceedings of the 37th Symposium on Theoretical Aspects of Computer Science (STACS 2020))
The canonical problem for the class Quantum Merlin-Arthur (QMA) is that of estimating ground state energies of local Hamiltonians. Perhaps surprisingly, [Ambainis, CCC 2014] showed that the related, but arguably more natural, problem of simulating local measurements on ground states of local Hamiltonians (APX-SIM) is likely harder than QMA. Indeed, [Ambainis, CCC 2014] showed that APX-SIM is P^QMA[log]-complete, for P^QMA[log] the class of languages decidable by a P machine making a logarithmic number of adaptive queries to a QMA oracle. In this work, we show that APX-SIM is P^QMA[log]-complete even when restricted to more physical Hamiltonians, obtaining as intermediate steps a variety of related complexity-theoretic results. We first give a sequence of results which together yield P^QMA[log]-hardness for APX-SIM on well-motivated Hamiltonians: (1) We show that for NP, StoqMA, and QMA oracles, a logarithmic number of adaptive queries is equivalent to polynomially many parallel queries. These equalities simplify the proofs of our subsequent results. (2) Next, we show that the hardness of APX-SIM is preserved under Hamiltonian simulations (a la [Cubitt, Montanaro, Piddock, 2017]). As a byproduct, we obtain a full complexity classification of APX-SIM, showing it is complete for P, P^||NP, P^||StoqMA, or P^||QMA depending on the Hamiltonians employed. (3) Leveraging the above, we show that APX-SIM is P^QMA[log]-complete for any family of Hamiltonians which can efficiently simulate spatially sparse Hamiltonians, including physically motivated models such as the 2D Heisenberg model. Our second focus considers 1D systems: We show that APX-SIM remains P^QMA[log]-complete even for local Hamiltonians on a 1D line of 8-dimensional qudits. This uses a number of ideas from above, along with replacing the "query Hamiltonian" of [Ambainis, CCC 2014] with a new "sifter" construction.

Nonlinear focal mapping of ferroelectric domain walls in LiNbO3: Analysis of the SHG microscopy contrast mechanism - Spychala, K. J.; Mackwitz, P.; Rüsing, Michael; Widhalm, A.; Berth, Gerhard; Silberhorn, Christine; Zrenner, Artur (Journal of Applied Physics)

Selbstreguliertes Lernen - Können die das überhaupt? Gestaltung von Lernprozessen in berufsvorbereitenden Bildungsgängen. - Sloane, Peter F. E.; Daniel, Desiree; Meier, Karin; Schwabl, Franziska; Volgmann, Simone

Material Specific Predicting of the Optimal Joining Parameters for the Screw Blind Rivet Joining Process - Moritzer, Elmar; Hillemeyer, Johannes (73rd Annual Assembly of International Institute of Welding (IIW) and International Conference)

MANUFACTURING OF HYBRID COMPONENTS BY VARTM-PROCESS USING NEW SEALING TECHNIQUE DEVELOPED - Chalicheemalapalli Jayasankar, Deviprasad; Stallmeister, Tim; Wang, Zheng; Tröster, Thomas (Hybrid 2020 Materials and Structures)

PSΦ: Forschungsprogramm zur Studieneingangsphase im Physikstudium - Bauer, Anna; Lahme, Simon; Woitkowski, David; Vogelsang, Christoph; Reinhold, Peter (PhyDid B – Didaktik der Physik – Beiträge zur DPG-Frühjahrstagung)

Vorerfahrungen, Einstellungen und motivationale Orientierungen als mögliche Einflussfaktoren auf den Einsatz digitaler Werkzeuge im naturwissenschaftlichen Unterricht - Vogelsang, Christoph; Finger, Alexander; Laumann, Daniel; Thyssen, Christoph (Zeitschrift für Didaktik der Naturwissenschaften)

Entwicklung von Professionswissen und Unterrichtsperformanz im Lehramtsstudium Physik. Analysen zu valider Testwertinterpretation - Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan (Zeitschrift für Pädagogik)
Angehende Physiklehrkräfte sollen im Rahmen ihres Studiums fachliches und fachdidaktisches Wissen erwerben, welches die Gestaltung lernförderlichen Unterrichts ermöglicht. Es ist allerdings empirisch nur wenig geklärt, wie sich dieses Wissen im Laufe des Studiums entwickelt und ob es zur Ausbildung von Handlungsfähigkeiten beiträgt. Um derartige Wirkungsaussagen treffen zu können, müssen Instrumente entwickelt werden, die eine valide Testwertinterpretation zulassen. In diesem Beitrag werden auf Basis von im Projekt Profile-P+ entwickelten Instrumenten Validitätsanalysen zur längsschnittlichen Entwicklung des Professionswissens von Physiklehramtsstudierenden im Verlauf des Bachelorstudiums und ihrer Fähigkeiten zur Planung und Reflexion von Physikunterricht sowie zum Erklären von physikalischen Sachverhalten vor und nach dem Praxissemester dargestellt. Neben Wissenstests kamen standardisierte Performanztests zum Einsatz. Die vorliegenden Ergebnisse sprechen dafür, dass die erhobenen Messwerte im Sinne von Wirkungsaussagen interpretiert werden können. (DIPF/Orig.)

Professionalisierung durch Portfolioarbeit – Ein Beitrag zur Erfassung der Reflexionskompetenz von Lehramtsstudierenden. - Stender, Jana; Schaper, Niclas; Vogelsang, Christoph; Watson, Christina (Lehrerbildung auf dem Prüfstand)

Performance-Oriented Testing and Training in Teacher Education - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Reinhold, Peter; Schecker, Horst; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Schröder, Jan

Reflexionskompetenz trainieren: Unterrichtsvideographie als Werkzeug zur fachdidaktischen Begleitung im Praxissemester - Vogelsang, Christoph (Praxissemester (Religion) in NRW: Bilanz und Perspektiven)

Integrated All Optical Sampling of Microwave Signals in Silicon Photonics - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (2019 International Topical Meeting on Microwave Photonics (MWP))
Optical sampling of pseudo random microwave signals with sinc-shaped Nyquist pulse sequences has been demonstrated in an integrated silicon photonics platform. An electronic-photonic, co-integrated depletion type silicon intensity modulator with high extinction ratio has been used to sample the microwave signal with a sampling rate, which corresponds to three times its RF bandwidth. Thus, a sampling rate of 21 GSa/s is achieved with a 7 GHz modulator, with 3 dBm of differential input power.

Integrated source-free all optical sampling with a sampling rate of up to three times the RF bandwidth of silicon photonic MZM - Misra, Arijit; Kress, Christian; Singh, Karanveer; Preussler, Stefan; Scheytt, Christoph; Schneider, Thomas (Opt. Express)
Source-free all optical sampling, based on the convolution of the signal spectrum with a frequency comb in an electronic-photonic, co-integrated silicon device will be presented for the first time, to the best of our knowledge. The method has the potential to achieve very high precision, requires only low power and can be fully tunable in the electrical domain. Sampling rates of three and four times the RF bandwidths of the photonics and electronics can be achieved. Thus, the presented method might lead to low-footprint, fully-integrated, precise, electrically tunable, photonic ADCs with very high-analog bandwidths for the digital infrastructure of tomorrow.

Midinfrared Birefringence of Liquid Crystals, Polarimetry, and Intensity Modulators - Atorf, Bernhard; Auf der Landwehr, Chris Holm; Rennerich, Roman; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry B)

Den Einsatz digitaler Medien im naturwissenschaftlichen Unterricht lehren - Untersuchung der Lehrinitiative Didaktik:digital im Spannungsfeld von standortübergreifender Wirkungsanalyse und standortspezifischer Evaluation - Vogelsang, Christoph (Hochschuldidaktik erforscht Qualität - Profilbildung und Wertefragen in der Hochschulentwicklung III)

Integrated transition edge sensors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Gerrits, Thomas; Lita, Adriana; Krapick, Stephan; Herrmann, Harald; Ricken, Raimund; Quiring, Viktor; Mirin, Richard; Nam, Sae Woo; Silberhorn, Christine; Bartley, Tim (APL Photonics)

Theory of an Optoelectronic Microwave Phase-locked Loop based on a MLL reference and MZM-based Optoelectronic Phase Detection - Bahmanian, Meysam; Scheytt, Christoph

Untersuchungen zum energetischen Verhalten von Kunststoffverarbeitungsprozessen auch im Rahmen von Energiemanagementsystemen - Gehring, Andreas

Entwicklung eines Modells zur Berechnung der initialen Aufschmelzvorgänge in gleichläufigen Doppelschneckenextrudern - Westhues, Kim Jacqueline